Penanganan Hukum bagi Pasangan Suami Istri Katolik yang Bermasalah selama Periode Agustus-Desember 2021 - Yohanes Servatius Lon Lon (Randang Tana - Jurnal Pengabdian Masyarakat, 2022)
This article describes the community service activities (PkM) carried out by a servant as an academic at the Indonesian Catholic University of Santu Paulus Ruteng and the Chairperson of the Ruteng Diocese Tribunal. The PkM activities that have been carried out are carrying out legal handling through the title of marriage cases at the Ruteng Diocese Tribunal from 12 (twelve) Catholic married couples who filed a lawsuit against their marriage. The 12 marriages and households of Catholic married couples who were clients of the PkM were destroyed and failed. From the results of the investigation and handling of marriage cases conducted by the Ruteng Diocese Tribunal Institution, it was found that failed marriages were rooted in the initial primary motivation of the married couple who were legally disabled from the start. There were 12 cases handled by the Tribunal from August – December 2021. All the marriages that were handled earlier were invalid and should not have happened. It is just that this is not appropriately detected early on, thus leading them to a family life that is not harmonious and broken. After going through the process of assisting this troubled family, it turns out that pastoral caretakers no longer promise to restore a marriage that has been shattered. So, one way out is through legal action. After pastoral assistance cannot resolve their problems, the handling process is carried out. The legal handling method starts from consultation, administrative examination of case submissions, case investigation, trial, conclusion making, and delivery of decisions and further legal and pastoral consequences of decisions taken. With this legal treatment, troubled couples can be freed from legal entanglements and marital problems.